Análise da transferência de calor e parâmetros térmicos em leito empacotado de fermentação em estado sólido - Sales, Éverton Holanda (2023)
Aiming at expanding the scale of solid-state fermentation processes (SSF), it is necessary to develop and improve appropriate bioreactors. Of note are the packed-bed bioreactors (PBBs), which have already been studied for the production of enzymes useful in the biofuel processing chain, such as cellulases for second-generation ethanol. However, one of the main problems in the operation of these bioreactors is the overheating of the bed, so that heat transfer studies in these systems are necessary. In this context, the objective of this project was to evaluate the thermal behavior of a bed packed with solid agro-industrial waste, with and without the occurrence of cultivation. For tests without cultivation, the bed was packed with the the humid substrate (mixture of sugarcane bagasse and wheat bran in a 3:7 weight ratio), but not inoculated. With the aid of thermocouples and a thermal imager, the radial thermal profiles were evaluated in a steady state, for a fixed bed height, with water flowing through the jacket and air percolating through the bed in co-current directions (water and air ascending) and counter-current (ascending air and descending water) and under flows of 175 and 350 L/h percolation of air saturated in humidity. Effective parameters were determined through the traditional two-parameter model, based on which modified dimensionless numbers were defined and calculated to allow a better thermal analysis of the system. For a given flow, the thermal parameters were higher for fluid flow in counter-current, as well as increased with the increase in air flowrate. The cultivation case study was the production of cellulases by Myceliophthora thermophila. During cultivation, transient temperature profiles were recorded at various radial and axial positions. With fluid flow through the jacket and percolating air again in co and counter-current, maximum temperature reached was around 52°C, around 7°C above the optimum for cultivation. Finally, to test a strategy to possibly mitigate the overheating of the system, cultivations were carried out with periodic reversal of the percolating air flow. Although the maximum temperature reached was the same, greater thermal homogeneity was observed in the bed, probably due to the better air distribution between the fermenting modules.